2019
DOI: 10.1016/j.athoracsur.2019.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Case Volume-to-Outcome Relationship in Minimally Invasive Esophagogastrectomy

Abstract: Background:Outcomes after open esophagectomy (OE) have been shown to depend on institution case volume. We aim to determine whether a similar relationship exists for minimallyinvasive esophagogastrectomy (MIE). Methods: Patients who had OE or MIE (excluding robotic procdures) between 2010 and 2013 in the National Cancer Database were included. Outcomes included 30-and 90-day mortality, length-of-stay, hospital readmission, margin positivity, and number of lymph nodes harvested. Logistic and linear regression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
0
13
0
2
Order By: Relevance
“…A total of 3012 studies were examined, and 23 comprising 293,159 minimally invasive oncologic surgeries met the inclusion criteria and were used for the descriptive analysis [ 4 , 5 , 6 , 7 , 8 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The study selection schema is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 3012 studies were examined, and 23 comprising 293,159 minimally invasive oncologic surgeries met the inclusion criteria and were used for the descriptive analysis [ 4 , 5 , 6 , 7 , 8 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The study selection schema is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 23 studies, gastrointestinal surgery was the most common surgery type (nine studies) [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], followed by genitourinary (seven studies) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], gynecologic (four studies) [ 4 , 5 , 6 , 7 ], hepatobiliary (two studies) [ 8 , 29 ], and thoracic (one study) surgeries [ 37 ]. In the gynecologic surgery group, two studies reported the outcomes of minimally invasive hysterectomy in endometrial cancer [ 4 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations